Pendeteksi Objek Berupa Sampah Di Area Kampus Telkom University - Iqbal Syaifullah Azhary; Prajna Deshanta Ibnugraha; Setia Juli Irzal Ismail (Journal of Applied Engineering and Social Science (JAESS), 2024)
Garbage is an item that is produced from human activities and other living things that are no longer used. Garbage willbecome an environmental problem if not managed this properly. The large activity from Telkom University students meansthat most students throw garbage inappropriately when they are on the campus. This garbage problem can make thecampus environment very uncomfortable, due to lack of trash cans in areas that are rarely traverse by people. there aremany technological tools that can help to detect garbage. Which one of this is machine learning. Machine learning is artificialintelligence that helps humans to make a system and one of them is an object detection system. By using machine learningfor object detection system, the campus can check garbage that is thrown away carelessly. In this final project, a system willbe built that can detect objects in the form of garbage through a camera using an experimental based method. As for thesystems and tools used, Yolov5 as the model of the system and Raspberry Pi as the main computer. The results obtainedfrom object detection system are to help the campus detecting garbage in Telkom University campus area.